2021
DOI: 10.3389/fcvm.2021.775753
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Variability as a Predictive Marker of Newly Developed Cardiovascular Events in Type 2 Diabetes

Abstract: Background: Cardiovascular disease (CVD) is associated with morbidity and mortality in patients with type 2 diabetes mellitus (T2D). However, the role of serum uric acid as a risk factor for developing cardiovascular disease is controversial. This study investigated whether uric acid variability was associated with new-onset symptomatic CVD in patients with T2D, requiring percutaneous coronary intervention.Methods: A total of 1,071 patients were enrolled in this retrospective cross-sectional study after propen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…UA identified was as a predictor for mortality, which is consistent with previous studies 24–27 . It is thought that high concentrations of UA in T2DM facilitated insulin resistance, DPN and cardiovascular disease, which were associated with mortality 28–31 . ALT was ranked as the second‐best for predictor of mortality.…”
Section: Discussionsupporting
confidence: 85%
“…UA identified was as a predictor for mortality, which is consistent with previous studies 24–27 . It is thought that high concentrations of UA in T2DM facilitated insulin resistance, DPN and cardiovascular disease, which were associated with mortality 28–31 . ALT was ranked as the second‐best for predictor of mortality.…”
Section: Discussionsupporting
confidence: 85%
“…Besides, evidence from previous studies indicated that high uric acid is independently associated with an increased risk of new-onset CVD in patients with diabetes ( 21 , 22 ). Which is consistent with our finding that keeping or rising to hyperuricemia was significantly associated with the incidence of cardiovascular diseases among patients with diabetes (OR, 1.67; 95% CI, 1.15, 2.44, P = 0.007).…”
Section: Discussionmentioning
confidence: 98%
“…However, as for CVD, other studies demonstrated the associations between SUA and CVD, for example, a prospective study, found that compared with individuals in the bottom third of baseline measurements of serum uric acid in the Reykjavik study, those in the top third had an age- and sex-adjusted odds ratio for CHD of 1.39 (95% CI, 1.23–1.58) ( 20 ). Evidence from the Third National Health and Nutrition Examination Survey revealed an increased risk of CV mortality with increasing SUA levels, hazard ratio (95% CI) per 59.5 mmol/l of SUA was 1.32 (1.25–1.38), and remained 1.15 (1.08–1.21) even after adjusted for demographic factors, comorbidities and other risk factors ( 21 ). The role of SUA as a risk factor for developing cardiovascular disease is controversial ( 22 ), and the association between SUA and CVD may be explained by its complex relationship with other cardiovascular risk factors ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the statistical analysis, study population, and adjusted covariates differed in the above-mentioned research. For instance, age, sex, eGFR, HbA1C, and duration of DM were adjusted in Seok Kang’s research [ 33 ], while systolic/diastolic blood pressure, serum lipid, and waist circumference were adjusted in Liu’s study [ 30 ], and our study additionally adjusted race, education levels, and poverty income ratio, which might lead to the different results. Participants involved in the above-mentioned research had different characteristics.…”
Section: Discussionmentioning
confidence: 99%